Financial Well-Being, Agile Work Behavior, Organizational Support, and Employee Performance: A Systematic Literature Review - Jeanette Dwi Setyorini; Intania Nurmara Nuzuari; Ismi Darmastuti; Eisha Lataruva (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Employee performance is a key determinant of organizational success, yet psychological, behavioral, and contextual factors beyond traditional management practices increasingly influence it. This study aims to systematically examine the relationships between financial well-being, agile work behavior, perceived organizational support, and employee performance, with a particular focus on the moderating role of perceived organizational support. A Systematic Literature Review was conducted following the PRISMA 2020 guidelines, analyzing 95 empirical studies published between 2016 and 2026. The findings indicate that agile work behavior consistently shows a positive relationship with employee performance across all reviewed studies, while financial well-being presents mixed and context-dependent effects, ranging from positive to non-significant relationships. Perceived organizational support generally strengthens the relationship between individual resources and performance, although in some contexts it may weaken or not significantly affect these relationships. The synthesis also reveals limited integration of financial well-being, agile work behavior, and perceived organizational support within a single conceptual model and a dominance of cross-sectional research designs. In conclusion, employee performance is shaped by the dynamic interaction of financial conditions, adaptive work behavior, and organizational support, highlighting the need for integrated models and context-sensitive approaches in future research.